Effect of gender differences and other factors on remuneration of employees in EU countries - Irena Antošová; Nad'a Hazuchová; Jana Stávková (DANUBE: Law, Economics and Social Issues Review, 2021)
The aim of the paper is to verify gender income differences and to reveal factors influencing differences in remuneration. Gender income differences across the EU range from 6% in Romania to 27% in the Czech Republic. Data from 178,878 employees filtered from the EU-SILC database were used for calculations. Stepwise regression analysis was used to identify factors that affect gender income differences. The greatest effect was shown in the "Absolute Income", then the "Job Change in the Last Year" factor, but the "Education" and "Age" showed a strongly negative tendency. Extraordinary attention is devoted to the effect of the "Job sector" factor, which also significantly contributes to the difference in income. Different representation of gender appears in different industries, which can be caused by preferences and be a consequence of persisting society-wide stereotypes. Social policies are not in line with changes in society and lag behind the development of society.
Keywords: 330; Job Remuneration; Income; Gender Pay Gap; Job Sector; EU-SILC